Community-Based Interventions for People Affected by Leprosy: A Narrative Review - Masala, Clausewitz Welmatus; Haroen, Hartiah; Pramukti, Iqbal (Media Publikasi Cendekia Indonesia, 2025)
This narrative review aims to explore community-based program interventions among patients with leprosy. This study employs the PCC (Population, Concept, Context) framework and collects data from six literature reviews accessed through the PubMed database. Keywords adjusted according to Medical Subject Headings (MeSH) terms (